The manager and the flexworker: An interpretive interactionist perspective - Julia Richardson (Management Revue, 2009)
Contemporary work arrangements are undergoing a dramatic transformation with increasing diversity in how work is done, by whom and where. This paper focuses on flexwork as an increasingly common work arrangement which changes the physical and relational dynamics between managers and employees. Drawing on a qualitative study of 'flexworkers' in a large MNC in Canada, it explores their relationships with their managers and vice versa. Located within an interpretive interactionist perspective, it highlights the centrality of interaction, identity construction and significant others and their influence on manager-employer relationships. It also explores and theorizes the relationships between flexworkers and their office-based colleagues.
Keywords: 650; flexworkers; teleworking; interpretive interactionism; management; qualitative